1987
DOI: 10.3109/02844318709083582
|View full text |Cite
|
Sign up to set email alerts
|

Facial Morphology and Occlusion At The Stage Of Early Mixed Dentition In Cleft Lip and Palate Patients Treated With Delayed Closure Of The Hard Palate

Abstract: Cephalometric radiographs and dental study casts were analyzed in a group of 23 seven-year-old cleft lip and palate patients, 16 with unilateral and 7 with bilateral cleft. The patients' primary surgical procedures had been completed except for closure of the cleft in the hard palate. For comparison, similar records from another group of patients, 18 with unilateral and 8 with bilateral cleft lip and palate, were studied. In these cases the cleft of the hard palate had been repaired in infancy, using a vomer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
2
8

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 6 publications
2
26
2
8
Order By: Relevance
“…The reason for delaying the repair of the hard palate has been to minimize interference from surgery with midfacial growth [1]. However, both clinical practice and research have gradually demonstrated that many of the children with open residual clefts in the hard palate have speech problems during the preschool and early school ages (before hard palate repair) with hypernasal resonance, air leakage and, particularly, a compensatory retracted oral articulation of anterior pressure consonants.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for delaying the repair of the hard palate has been to minimize interference from surgery with midfacial growth [1]. However, both clinical practice and research have gradually demonstrated that many of the children with open residual clefts in the hard palate have speech problems during the preschool and early school ages (before hard palate repair) with hypernasal resonance, air leakage and, particularly, a compensatory retracted oral articulation of anterior pressure consonants.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of two-stage palate closure also became established with slight variations in other predominantly European cleft centers (Hotz et al, 1978;Ross, 1987a;Shaw et al, 1992;Noverraz et al, 1993;Friede and Enemark, 2001;Nollet et al, 2005), though they remained a minority. Opinions in favor of two-stage palate closure were mainly expressed by cleft centers that had carried out this surgical protocol over a relatively long period (Hotz et al, 1978;Friede et al, 1980Friede et al, , 1987Gnoinski, 1991;Friede and Enemark, 2001). They maintain that less growth inhibition in the jaw and midface expresses itself in various ways, that is, there were fewer anterior (Hotz et al, 1978) and lateral crossbites in both deciduous (Friede et al, 1980) and mixed dentition (Friede et al, 1987), and that to a certain extent a more favorable sagittal upper and lower jaw relation is observed in the lateral cephalogram (Hotz et al, 1978;Friede et al, 1987;Friede and Enemark, 2001).…”
mentioning
confidence: 99%
“…With respect to dental arch dimensions and occlusion in BCLP patients, only a few longitudinal studies with a sufficient number of patients can be found in the literature (Larson et al, 1983;Bishara et al, 1985;Athanasiou et ai, 1987;Friede et al, 1987;Hotz et al, 1987). Larson et al (1983) evaluated the dental occlusion in the deciduous dentition of 19 children with bilateral clefts who underwent orthopaedic treatment and early bone grafting before orthodontic treatment and after starting orthodontic treatment (about 10 years of age).…”
Section: Introductionmentioning
confidence: 99%
“…Mandibular arch dimensions seemed to be affected by the changes in the maxillary arch. Friede et al (1987) studied two different treatment approaches concerning hard palate closure in 15 BCLP patients. Due to the relatively large variation in maxillary morphology and the small number of patients studied, no differences in facial morphology and occlusion between subgroups could be found.…”
Section: Introductionmentioning
confidence: 99%